2022
DOI: 10.1111/jace.18850
|View full text |Cite
|
Sign up to set email alerts
|

Predicting initial dissolution rates using structural features from molecular dynamics simulations

Abstract: Predicting the chemical durability of glass materials is important for various applications from daily life such as cell phone screens and kitchenware to advanced technologies such as nuclear waste disposal and biomedicine. In this work, we explored the prediction of the initial glass dissolution rates using structural features from molecular dynamics (MD) simulations for a series of glass compositions (total 28), including ZrO 2 -and V 2 O 5 -containing boroaluminosilicate, borosilicate, and aluminosilicate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…139 MD-based QSPR is mostly limited by the potential parameter developments, as well as the lack of bond energy information, as discussed previously. 60 Despite the ability of MD to simulate glasses containing oxides with multiple oxidation states (as demonstrated in studies on vanadium 120,130 and iron 195 ), the knowledge of the quantity of each oxidation state through experimental input is necessary. Furthermore, generating MD simulated structures of hundreds or thousands of glasses with a consistent simulation process requires significant computing resources, as it was found that system size and cooling rate have impacts on final simulated structures.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 4 more Smart Citations
“…139 MD-based QSPR is mostly limited by the potential parameter developments, as well as the lack of bond energy information, as discussed previously. 60 Despite the ability of MD to simulate glasses containing oxides with multiple oxidation states (as demonstrated in studies on vanadium 120,130 and iron 195 ), the knowledge of the quantity of each oxidation state through experimental input is necessary. Furthermore, generating MD simulated structures of hundreds or thousands of glasses with a consistent simulation process requires significant computing resources, as it was found that system size and cooling rate have impacts on final simulated structures.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The initial dissolution rate (r 0 ) model, shown in Figure 6, used both pH and structural features obtained from MD, whereas using glass compositions alone was insufficient to represent measured data. 60 With these many options available as model features, feature selection analysis is the next important aspect in terms of model fitting. SHapley Additive exPlanations (SHAP) is a model-agnostic method for explaining individual predictors of ML models.…”
Section: Model Features/termsmentioning
confidence: 99%
See 3 more Smart Citations